Digital Culture and Community Empowerment: Capacity Building for MSMEs and Artisans in Kemijen - Ekawati Marhaenny Dukut; Monik Palupi Murniati; Angelika Riyandari (Celt: A Journal of Culture, English Language Teaching and Literature, 2025)
This article discusses how digital culture can help empower communities by supporting Micro, Small, and Medium Enterprises (MSMEs) and local artisans in Kemijen, East Semarang, Central Java, Indonesia. The program employed a Participatory Action Research (PAR) method to provide digital literacy training with a focus on promotion through the social media platforms. Participants of the program included mostly female MSME entrepreneurs producing milkfish (bandeng), mochi cakes, rice box (nasi kotak), and coconut crushed ice cream (es puter) contents promoted on Instagram and Facebook. In addition, there were also Javanese dancers, a batik artisan, and keroncong musicians whose cultural practices were incorporated into promotional content on YouTube. The program demonstrated both benefits and challenges. The goal was to improve skills in financial recording and digital storytelling on social media, but maintaining participant motivation was challenging. Most of the female entrepreneurs and creative artisans were hesitant to fully embrace digital tools. Unfortunately, the young people with digital knowledge were not interested in managing social media accounts. Therefore, the goal of reaching a broad online audience was only partially achieved. Nonetheless, the participatory approach helped raise awareness of digital opportunities, fostered intergenerational collaboration, and opened discussions about using social media to connect cultural heritage with the digital marketplace. By engaging community members as co-creators, the PAR method shows that true empowerment requires more than just technical training. It requires long-term mentoring, motivation, and shared responsibility. Therefore, follow-up programs are recommended. The digital and community cultural empowerment capacity-building initiative for MSMEs and creative artisans in Kemijen suggests that combining cultural identity with digital promotion through social media can transform local products and tradition into useful tools for economic growth while preserving cultural heritage